Prevalence and Patterns of Pneumonia in Histopathology of Lungs from Qurban Cattle (Bos spp.) in Lampung, Indonesia (2019): A Laboratory-Based Survey - Nursafitri, Umy; Sutyarso; Susanto, Gregorius Nurgroho; Widiastuti, Endang Linirin (ISEJ : Indonesian Science Education Journal, 2024)
Pneumonia in cattle compromises welfare and carcass value, yet abattoir-based histopathology evidence from Indonesia’s qurban context remains scarce. To estimate the prevalence of pneumonia and characterize lesion patterns in lungs from qurban cattle processed in Lampung Province (2019). A cross-sectional, laboratory study analyzed 20 bovine lungs collected opportunistically from four districts (Bandar Lampung, Lampung Timur, Pringsewu, Metro). Representative tissues were fixed in 10% neutral buffered formalin, paraffin-embedded, sectioned at 4–5 µm, and stained with hematoxylin–eosin; bright-field microscopy (≈40×–400×) classified lesions a priori as interstitial pneumonia, bronchopneumonia, or aspiration-consistent pneumonia, and annotated severity (mild/moderate), temporality (acute/chronic), and distribution (focal/multifocal). Analyses were descriptive. 13/20 (65%) lungs met histological criteria for pneumonia, while 7/20 were normal. Interstitial cases showed alveolar-septal thickening, congestion/hemorrhage, and alveolar edema; bronchopneumonia was airway-centered with peribronchiolar cuffing and suppurative/fibrinosuppurative exudates; aspiration-consistent lesions exhibited focal/multifocal cranioventral involvement with foreign particulate material and neutrophilic exudates, occasionally with multinucleated giant cells. Most lesions were mild–moderate and predominantly acute. The profile indicates a multifactorial aetiology in which upstream infectious processes and perimortem handling both contribute, underscoring the added value of histopathology over gross inspection alone. Findings support immediate refinement of slaughter procedures (restraint, incision sequence, head positioning) to reduce aspiration risk; routine integration of histopathology paired with culture/PCR into abattoir surveillance for actionable supplier feedback; and periodic, micrograph-based auditing and training to strengthen food safety, animal welfare, and biosecurity.